Solitary fibrous tumour of lacrimal sac masquerading as lacrimal sac mucocele: a diagnostic and surgical dilemma. Issue 5 (17th May 2022) - Panda, Bijnya Birajita; Viswanath, Shilpa; Baisakh, Manas; Rauta, Sudhasmita
Abstract : Swellings in medial canthal area in eye most often involve the lacrimal sac, the commonest aetiology being chronic dacryocystitis. Very rarely, there is a deviation in the routine diagnosis when the pathology comes out to be a lacrimal sac tumour. We report the case of a young man who presented with a medial canthal mass not extending above the medial canthal ligament. The clinical presentation was typical for a lacrimal sac mucocele, however on histopathological evaluation was diagnosed as a rare case of solitary fibrous tumour of lacrimal sac. We recommend radiological investigation in medial canthal masses where there is negative regurgitation on pressure over lacrimal sac area to avoid misdiagnoses.